Development of an in vitro Model for the Study of the Response of Equine Tendon Fibroblasts to Injury and Medication - Dahlgren, L. A.; Rosenbusch, R. F.; Booth, L. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Equine tendon fibroblasts were isolated from explants of superficial digital flexor tendon, subcultured and maintained in monolayers. The cells were characterized by light microscopy, electron microscopy and radiolabel studies for proteoglycan production. Two predominant cell morphologies were identified. The cells dedifferentiated toward a more spindle shape with repeated subcultures. Equine tendon fibroblasts were successfully cryopreserved and subsequently subcultured. The ability to produce proteoglycan was preserved.The isolated cells were identified as fibroblasts, based on their characteristic shape by light microscopy and ultrastructure and the active production of extracellular matrix proteins. Abundant rough endoplasmic reticulum and the production of extracellular matrix products demonstrated active protein production and export. Proteoglycans were measurable via liquid scintillation counting in both the cell-associated fraction and free in the supernatant. This model is currently being utilized to study the effects of polysulfated glycosaminoglycan on tendon healing. Future uses include studying the effects of other pharmaceuticals, such as hyaluronic acid, on tendon healing.A model was developed for in vitro investigations into tendon healing. Fibroblasts were isolated from equine superficial digital flexor tendons and maintained in monolayer culture. The tenocytes were characterized via light and electron microscopy. Proteoglycan production was measured, using radio-label techniques. The fibroblasts were cryopreserved and subsequently subcultured. The cells maintained their capacity for proteoglycan production, following repeated subculturing and cryopreservation.
Keywords: Tendinitis; cell culture; tendon fibroblast